EFFICIENCY FACTORS OF THE VERTICAL INTEGRATION STRATEGY - N. Maslennikova (Вестник университета, 2017)
The purpose of the article is to define the saving factors of vertical integration strategy. The subject of study is the compilation of various types of activities in the value chain frame. The article contains the list of saving factors of vertical integration strategy implementation: price reduction, management and operational cost savings, opportunities of innovative development and science-based production output, the savings of current assets, investments, improvement of the personnel social protection and so on. The conclusion: vertical integration strategy leads to the creation of science-based products with high value added share that helps to move from raw resource economy to resource saving and independent of imports economy.